Mushanokōji Saneatsu in the Eyes of Contemporaries - Zaberezhnaya O. A. (Ежегодник Япония, 2021)
The personality of Mushanokōji Saneatsu (1885–1976), a writer, thinker, poet, playwright, and artist, the ideological inspirer of neo-humanism in Japan in the early 20th century, cannot be ignored in the history of Japanese literature and culture as a whole. In this paper, we aim to explain the fact of such a wide popularity of Mushanokōji and such a strong influence of his personality on his contemporaries. To answer this question, we compiled a description of Mushanokōji, based on the memories of people personally acquainted with him. Having examined the childhood and youth of Mushanokōji as a period of the formation of his character and ideological preferences, the beginning of his career, we turned to the characteristics given by Mushanokōji’s contemporaries: his associates in the Shirakaba group, participants of the New Village project, and literary critics. We found that Mushanokōji did not consider any family member of his to be a role model, preferring to follow the distant ideals of Tolstoy, Rodin, Cezanne, and others. From a young age, Mushanokōji, realizing his unattractiveness and encountering various difficulties in his projects, drew strength from his inherent naive optimism, firm faith in his lucky star, and his uniqueness and sincere sense of humor. These qualities were celebrated by his acquaintances throughout his life. However, Mushanokōji’s popularity is most due to his natural magnetism. As follows from a lot of evidence, Mushanokōji had the ability to attract people in a first meeting, during a conversation or a public speech. His positive energy, which infected and inspired others, allowed some to even see in his figure a religious leader who could direct seekers on the right creative path. Therefore, we can conclude that the genius of Mushanokōji was not only in his literary ability, but primarily in his becoming an iconic figure of his epoch.